2015
DOI: 10.1111/his.12840
|View full text |Cite
|
Sign up to set email alerts
|

Tubulocystic renal cell carcinoma is an entity that is immunohistochemically and genetically distinct from papillary renal cell carcinoma

Abstract: Pure tubulocystic renal cell carcinoma is an indolent tumour with a good prognosis. Our data support the distinction of this neoplasm as a separate entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 22 publications
(88 reference statements)
0
16
0
Order By: Relevance
“…Since the tumor is composed of cells with abundant granular cytoplasm, the differential includes clear cell/conventional RCC, papillary RCC, chromophobe RCC, oncocytoma, hereditary leiomyomatosis associated RCC, and succinate‐dehydrogenase B deficiency associated RCC (Table ). The differential also includes several lesions other than RCC, including normal proximal tubular cells, granular cell tumor, angiomyolipoma, and xanthogranulomatous pyelonephritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the tumor is composed of cells with abundant granular cytoplasm, the differential includes clear cell/conventional RCC, papillary RCC, chromophobe RCC, oncocytoma, hereditary leiomyomatosis associated RCC, and succinate‐dehydrogenase B deficiency associated RCC (Table ). The differential also includes several lesions other than RCC, including normal proximal tubular cells, granular cell tumor, angiomyolipoma, and xanthogranulomatous pyelonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…Tubulocystic renal cell carcinoma (RCC) is a rare (<100 cases reported in the literature), recently described variant of RCC with a relatively indolent prognosis, though bone metastases have been reported . This tumor is composed a variably sized tubules and cysts lined by a single layer of cells with relatively abundant granular, eosinophilic cytoplasm, and large round nuclei with relatively prominent nucleoli embedded in an evenly fibrotic stroma.…”
Section: Introductionmentioning
confidence: 99%
“…Tubulocystic RCC (TC-RCC) is a relative new entity first officially included in the 2012 ISUP Vancouver Classification. Similar to MTSCC, TC-RCC has morphologic and immunohistochemical features that are frequently overlap with PRCC [36,96,97].…”
Section: Tubulocystic Renal Cell Carcinoma (Tc-rcc)mentioning
confidence: 99%
“…The genetic features of these tumors are variable with previous studies suggesting similar CNV patterns to that reported in type 1 PRCC (gain of chromosome 7 or 17 and loss of Y). However, more recent studies showed that gain of chromosomes 7 and 17 is not a typical CNV pattern in cases of TC-RCC where strict histo-diagnostic criteria are applied [96][97][98]. In fact, loss of chromosome 9 has been suggested as a characteristic feature of TC-RCC [99].…”
Section: Tubulocystic Renal Cell Carcinoma (Tc-rcc)mentioning
confidence: 99%
“…However, some categories still labeled as "carcinoma", including clear cell papillary renal cell carcinoma (CCPRCC), renal angioleiomyomatous tumor (RAT), and tubulocystic carcinoma (TCRCC), all with a particularly good prognosis when diagnosed as low stage (pT1a), show no malignant behavior: in fact, no metastases have been reported in these categories when surgically excised [5][6][7][8][9][10][11][12][13][14]. RAT is also considered by most authors as a morphologic variation of CCPRCC [15][16][17].…”
Section: Introductionmentioning
confidence: 99%